Data mining reveal the association between diabetic foot ulcer and peripheral artery disease - Jie Zou; Jie Zou; Jie Zou; Wen Zhang; Wen Zhang; Xiaoming Chen; Xiaoming Chen; Wenxing Su; Wenxing Su; Daojiang Yu; Daojiang Yu (Frontiers Media S.A., 2022)
BackgroundDiabetic foot ulcer (DFU) and peripheral artery disease (PAD) are common diseases that seriously affect the quality of life and bring a huge economic burden to society. Although mounting evidence supports a close link between the two disorders, the mechanisms of comorbidity remain to be fully elucidated.MethodsThe gene expression profiles of DFU (GSE80178) and PAD (GSE100927) were downloaded from the Gene Expression Omnibus (GEO) database. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) performed pathway enrichment analysis for common differentially expressed genes (DEGs) present in DFU and PAD. Subsequently, we constructed a protein-protein interaction (PPI) network using the STRING database and detected core modules and hub genes in the network. Finally, we analyzed the co-expression network and the TF-miRNA-mRNA regulatory network of hub genes.ResultsA total of 167 common DEGs (91 up-regulated genes and 76 down-regulated genes) was selected for subsequent analyses. Functional analysis emphasizes the important role of chemokines and cytokines in these two diseases. Finally, six hub genes were identified using cytoHubba, including CXCL8, IL1RN, MMP1, CD68, CCR7 and CCL3.ConclusionsThe hub genes and signaling pathways involved can regulate both diseases simultaneously, suggesting a close relationship between the molecular mechanisms of the two diseases and possible targets for drugs that intervene in both diseases.